A proposal for an inclusive working definition of genetic discrimination to promote a more coherent debate - Kaiser, Beatrice; Uberoi, Diya; Raven-Adams, Maili C.; Cheung, Katherine; Bruns, Andreas; Chandrasekharan, Subhashini; Otlowski, Margaret; Prince, Anya E. R.; Tiller, Jane; Ahmed, Arzoo; Bombard, Yvonne; Dupras, Charles; et al. (Nature genetics, 2024)
Genetic discrimination is an evolving phenomenon that impacts fundamental human rights such as dignity, justice and equity. Although, in the past, various definitions to better conceptualize genetic discrimination have been proposed, these have been unable to capture several key facets of the phenomenon. In this Perspective, we explore definitions of genetic discrimination across disciplines, consider criticisms of such definitions and show how other forms of discrimination and stigmatization can compound genetic discrimination in a way that affects individuals, groups and systems. We propose a nuanced and inclusive definition of genetic discrimination, which reflects its multifaceted impact that should remain relevant in the face of an evolving social context and advancing science. We argue that our definition should be adopted as a guiding academic framework to facilitate scientific and policy discussions about genetic discrimination and support the development of laws and industry policies seeking to address the phenomenon.
Gesehen am 20.02.2025